Related Posts

This Post Has 4 Comments

  1. dc=6 square root of 3 and ac is 12 square root 3

    c and d

    step-by-step explanation:

    square root of 3/2 = 18/c

    cross multiply to get 18*2=√3*c

    36/√3 * √3/√3 = c

    c= 36*√3/3

    c=12√3

  2. Answer: b 2 = 1.

    step-by-step explanation: given equation a = h(b 1+b 2)

    also we are given values of a, h and b 1 as :

    a = 16, h = 4, and b 1 = 3.

    in order to solve it for b 2, we need to plug the given values of   a, h and b 1 .

    therefore, plugging values of   a, h and b 1   in given equation, we get

    16 = 4( 3 + b 2)

    first dividing both sides by 4, we get

    [tex]\frac{16}{4}   =\frac{4( 3 + b 2)}{4}[/tex]

    4 = 3 + b 2

    subtracting 3 from both sides, we get

    4 -3 = 3 -3 + b 2

    1 = b 2.

    therefore, b 2= 1.

Leave a Reply

Your email address will not be published. Required fields are marked *